Brinjal (Solanum melongena) rootstocks improve photosynthetic rate, fruit yield and quality parameters in grafted tomato (Solanum lycopersicum) - ANANT BAHADUR; HARE KRISHNA; RAJEEV KUMAR; ANISH KUMAR SINGH; SAPANA YADAV; T K BEHERA (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during winter (rabi) seasons of 2021–22 and 2022–23 at ICAR-Indian Institute of Vegetable Research, Varanasi, Uttar Pradesh to study the improvement in yield and quality parameters in tomato (Solanum lycopersicum L.) cultivar using brinjal (Solanum melongena L.) rootstock. Three improved cultivars of tomatoes i.e. Kashi Aman, Kashi Adarsh and Kashi Chayan were grafted over three brinjal rootstocks, IC-111056, IC- 354557, and Surya. Experimental findings revealed that brinjal rootstocks significantly affected photosynthetic traits, root architectures, fruit yields and quality traits of tomatoes. Maximum photosynthetic rate (23.8 µmol/m2/s) and stomatal conductance (492.74 mmol/m2/s) were recorded in Kashi Chayan grafted over Surya rootstock, whereas chlorophyll fluorescence yields (Fv/Fm) was significantly higher in Kashi Aman self-rooted plants (0.452–0.457). Grafting tomato onto brinjal rootstocks significantly enhanced most of the yield traits, such as fruit number, weight, size and yields. Surya + Kashi Chayan graft combination registered an enhancement in number of fruits and yields by 8.65% and 8.4%, respectively over self-rooted Kashi Chayan. Significantly higher root volumes were noticed in two graft combinations i.e. IC-354557 + Kashi Aman (28.53 cm2) and Surya + Kashi Chayan (27.98 cm2), while 63% and 44.5% higher root length density (RLD) were registered in graft combinations IC-354557 + Kashi Chayan and Surya + Kashi Chayan, respectively over self-rooted Kashi Chayan. Fruit quality such as lycopene and ascorbic acid contents were significantly affected in different rootstocks and scions, whereas fruit acidity was unaffected. From the present study it may be conclude that use of brinjal rootstock Surya significantly improved most of the physiological, yield, root architecture and fruit quality in Kashi Chayan tomato cultivars.